Proses Penyidikan Dalam Penyelesaian Tindak Pidana Kekerasan Dalam Rumah Tangga Yang Dilakukan Oleh TNI-AD (Studi Di Pengadilan Militer I-02 Medan) - Fadhlurrahman Fadhlurrahman; Rafiqi Rafiqi; Arie Kartika (Universitas Medan Area, 2019)
Domestic violence perpetrated by individual soldiers not only harmed their families but also caused losses to the soldiers themselves both morally and materially. Proving a criminal offense, the process of investigation, prosecution, and examination in a court of law in a case of a crime of domestic violence is carried out according to the provisions of the applicable criminal procedure law. This type of research is normative law that is analyzing a decision made by combining primary data legal materials with secondary data obtained in the field with interviews. The investigation process in which the Military Police conduct an investigation of suspects with military status and refers to Law Number 31 of 1997 concerning the Military Criminal Code where eventually the case files will be submitted to military prosecutors for trial in military court. There are 4 stages in the process of resolving cases in the military court in the investigation stage, the prosecution stage, the hearing stage in the trial, the decision implementation stage. The form of criminal liability for military members who commist crimes is regulated in Article 6 of the Military Criminal Code.